Simple colorimetric method for cholinesterase-inhibitor screening in gastric content by using phytoesterase enzyme from kidney bean - Thanawat Kaewmaroeng (2020)
© 2020 Thanawat Kaewmaroeng et al. Background and Objective: Diagnosis of cholinesterase inhibitor insecticide ingestion is based on clinical suspicious and should be confirmed by cholinesterase essay. However, serum cholinesterase activity test requires specific instruments and procedure. This study aimed to develop simple colorimetric test to detect cholinesterase inhibitors in the gastric content, using phytoesterase and alpha naphthyl acetate as a chromogenic substrate. Materials and Methods: Methomyl and chlorpyrifos were selected for the phytoesterase enzyme inhibition assay. The experiment was conducted using pooled insecticide-free gastric content sample from ten cadavers. The gastric content samples were prepared by simple filtration procedure or liquid-liquid extraction procedure with dichloromethane or ethyl acetate. The inhibitor concentrations measured by the developed phytoesterase enzyme inhibition assay were compared with those analyzed by the LC-MS/MS and the GC-FPD. Results: Different sample preparation procedures, sensitivity and specificity and specificity of the test were investigated. Sample extracted with dichloromethane reduced the effect of matrix in gastric content as same as ethyl acetate. The developed color test method of detection showed 56.52% sensitivity and 100% specificity for methomyl, 100% sensitivity and 96.30% specificity for chlorpyrifos. The limit of detection of the assay was 422.6 ng mL-1 for methomyl and was 339.8 ng mL-1 for chlorpyrifos. Conclusion: This developed method could be used an alternative diagnostic test for methomyl and chlorpyrifos self-ingestion.